The Journal Of Muamalat and Islamic Finance Research : Empowering the Peripheral Ummah Through Waqf - Mohd Adib Ismail, Nik Mohd Azim Nik Ab Malik (UNIVERSITI SAINS ISLAM MALAYSIA (USIM), 2015)
The peripheral ummah is the community that is excluded socially and economically from the market system. Therefore, partial influence